KOMPETENSIYAVIY YONDASHUV ORQALI BOʻLAJAK OʻQITUVCHILARDA TANQIDIY FIKRLASHNI RIVOJLANTIRISH TEXNOLOGIYASINI TAKOMILLASHTIRISH (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article widely analyzes the improvement of technologies for developing critical thinking in future teachers through a competency-based approach. It discusses the essence of critical thinking, teaching strategies, reflective practice, problem-based learning and digital competencies as core mechanisms for pedagogical development.